Effect of Methadone or Hydromorphone on Cardiac Conductivity in Dogs Before and During Sevoflurane Anesthesia - Keating, Stephanie; Fries, Ryan; Kling, Katherine; Graham, Lynelle; Clark-Price, Stuart; Schaeffer, David J. (Frontiers in Veterinary Science, 2020)
Objective: To evaluate changes in electrocardiogram (ECG) variables in healthy dogs receiving either methadone or hydromorphone IV before and during sevoflurane anesthesia. Study Design: Prospective clinical study. Animals: Forty client-owned dogs. Methods: Dogs were randomized to receive methadone 0.5 mg/kg IV or hydromorphone 0.1 mg/kg IV in each part of a two-part study. In part one, dogs received the opioid prior to sevoflurane anesthesia (groups MS, n = 12 and HS, n = 12). Anesthesia was induced with propofol IV, maintained with sevoflurane, and dogs were mechanically ventilated. Standard 6-lead ECG recordings were obtained before opioid administration, 2, 5, and 10 min after opioid administration prior to anesthesia, and during anesthesia 15 min after end-tidal sevoflurane stabilized at 2.4%. In part two, conscious dogs received the same opioid treatments and ECGs were obtained at equivalent time points without undergoing anesthesia (groups M, n = 8 and H, n = 8). Values for ECG variables were determined by a blinded cardiologist and included: Heart rate (HR), PR interval, QT interval, and HR corrected QT interval (QTc) using the Bazett (QTcB), Fridericia (QTcF), and Van de Water (QTcV) formulas. Differences over time and between all four groups were evaluated using ANOVA for repeated measures with significance set at p ≤ 0.05. Results: Both methadone and hydromorphone administration reduced HR and prolonged PR and QT intervals, with greater changes observed during sevoflurane anesthesia. The greatest prolongation in QT interval was observed in dogs administered methadone during sevoflurane anesthesia. Conclusions and Clinical Relevance: Methadone and hydromorphone caused disturbances in myocardial electrical activity, and the addition of sevoflurane enhanced these disturbances. Both drugs caused considerable QT interval prolongation into the proarrhythmogenic range, with methadone causing greater prolongation.